PERILAKU JAJAN PADA ANAK SEKOLAH DASAR - Siti Qorrotu Aini (Jurnal Litbang: Media Informasi Penelitian, Pengembangan dan IPTEK, 2019)
ENGLISHSnacking behavior is very inherent in elementary school pupils. This study aims to describe the behavior of student’s snacking in elementary schools in the study location. The type of this research is descriptive one. The samples of this research were students of 5th grade. The research used purposive sampling. The number of samples included 68 students. The data in the research consisted of the habits of children's snacking at school and other habits related to snacking behavior. The data were obtained from survey by using questionnaire. The results showed that the majority of students ate snacks at school. Students had breakfast and they did not bring food to school. The student spends averagely IDR 4,000-IDR 5,000.00 to buy snacks per day. Some students buy snacks in the cafeteria or vendors around the school. The students buy snacks averagely 2 times a day during school breaks. Most students usually washed their hands before eating, however some students ever get sick after consuming snacks. Almost all elementary school students in the study area buy snacks even though they are accustomed to have breakfast. Food snacks are also widely bought by students who did not bring food to school. INDONESIAPerilaku jajan sangat melekat pada anak sekolah dasar. Penelitian ini bertujuan untuk menggambarkan perilaku jajan siswa di Sekolah Dasar dilokasi studi. Jenis penelitian ini adalah penelitian deskriptif. Sampel penelitian ini adalah siswa kelas 5. Pengambilan sampel dilakukan dengan purposive sampling. Jumlah sampel sebanyak 68 siswa. Data yang dikumpulkan meliputi kebiasaan jajan anak di sekolah dan kebiasaan lain yang berhubungan dengan kebiasaan jajan. Data diperoleh dari hasil pengisian kuesioner. Hasil penelitian menunjukkan bahwa sebagian besar siswa mengonsumsi jajanan di sekolah. Siswa terbiasa mengonsumsi sarapan dan tidak membawa bekal makanan ke sekolah. Rata-rata siswa menghabiskan uang sebesar Rp4.000,00-Rp5.000,00 per hari untuk membeli makanan jajanan. Sebagian siswa membeli jajanan di kantin atau penjaja di sekitar sekolah. Rata-rata siswa jajan 2 kali dalam sehari pada waktu istirahat sekolah. Sebagian besar siswa terbiasa mencuci tangan sebelum makan, meskipun demikian sebagian siswa pernah sakit setelah mengonsumsi jajanan. Hampir semua Siswa SD di lokasi studi membeli makanan jajanan meskipun  terbiasa makan pagi. Makanan jajanan juga banyak dibeli oleh siswa yang tidak membawa bekal makanan ke sekolah.